2008
DOI: 10.1097/nen.0b013e318180ec2e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolethalus Syndrome

Abstract: Hydrolethalus syndrome is a lethal malformation syndrome with a severe brain malformation, most often hydrocephaly and absent midline structures. Other frequent findings are micrognathia, polydactyly, and defective lobation of the lungs. Hydrolethalus syndrome is inherited in an autosomal recessive manner and is caused by a missense mutation in the HYLS1 gene. Here, we report the neuropathologic features of 21 genetically confirmed cases. Typically, 2 separated cerebral hemispheres could be identified, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, a precise analysis of the forebrain is rarely possible in fetuses with severe ciliopathies such as Meckel syndrome. Microphthalmia and benign tumors called diencephalic or hypothalamic hamartomas have been observed in Meckel syndrome and other ciliopathies (Ahdab-Barmada and Claassen, 1990; Roume et al, 1998; Paetau et al, 2008; Poretti et al, 2011, 2017; Del Giudice et al, 2014). Interestingly, diencephalic hamartomas have been linked to mutations in GLI3 and other SHH pathway genes (Shin et al, 1999; Hildebrand et al, 2016), suggesting that those observed in ciliopathies could also be caused by defects in SHH signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, a precise analysis of the forebrain is rarely possible in fetuses with severe ciliopathies such as Meckel syndrome. Microphthalmia and benign tumors called diencephalic or hypothalamic hamartomas have been observed in Meckel syndrome and other ciliopathies (Ahdab-Barmada and Claassen, 1990; Roume et al, 1998; Paetau et al, 2008; Poretti et al, 2011, 2017; Del Giudice et al, 2014). Interestingly, diencephalic hamartomas have been linked to mutations in GLI3 and other SHH pathway genes (Shin et al, 1999; Hildebrand et al, 2016), suggesting that those observed in ciliopathies could also be caused by defects in SHH signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Aspartylglycosaminuria (AGU) Palo and Mattsson (1970) and Haltia et al (1975) Infantile neuronal ceroid lipofuscinosis (CLN1) , Haltia, Rapola, Santavuori and Keranen (1973) and Santavuori et al (1973) Late infantile neuronal ceroid lipofuscinosis (CLN5) See Mole and Haltia (2015) Progressive epilepsy with mental retardation (CLN8) See Mole and Haltia (2015) Congenital neuronal ceroid lipofuscinosis (CLN10) See Mole and Haltia (2015) Progressive myoclonus epilepsy (EPN1) Haltia, Kristensson, and Sourander (1969) and Koskiniemi, Donner, Majuri, Haltia, and Norio (1974) Progressive encephalopathy with oedema, hypsarrhythmia and optic atrophy (PEHO) Haltia and Somer (1993) and Salonen, Somer, Haltia, Lorentz, and Norio (1991) Muscle-eye-brain disease (MEB) Haltia et al (1997) and Santavuori et al (1998) Hydrolethalus syndrome Paetau et al (2008) Infantile onset spinocerebellar ataxia (IOSCA) Koskinen et al (1994) and Lonnqvist, Paetau, Nikali, Boguslawski, and Pihko (1998) Foetal motoneuron disease Nousiainen et al (2008) T A B L E 1 Early-onset neurological disorders discovered and/or characterized by Finnish investigators (Kalimo et al, 1988) and tibial muscular dystrophy (Udd et al, 1998). The latter condition is caused by mutations in the gene encoding the giant skeletal-muscle protein, titin (Hackman et al, 2002).…”
Section: Disease Referencesmentioning
confidence: 99%
“…However, no cases of hydrolethalus syndrome with a molecular diagnosis have been associated with HPE. A review of 21 cases with molecularly confirmed variants in the gene HYLS1 found that all cases had a complete interhemispheric fissure, and in a few cases, a hypothalamic hamartoma was found (Paetau et al, 2008). Holoprosencephaly is not a common finding in hydrolethalus syndrome.…”
Section: Syndromes Without Molecular Diagnosesmentioning
confidence: 99%